2019
DOI: 10.2480/agrmet.d-18-00041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overnight radiation with monochromatic far-red and blue light on flower budding and expression of flowering-related and light quality-responsive genes in <I>Eustoma grandiflorum</I>

Abstract: The effects of overnight radiation with monochromatic light on flower budding using far-red-and blue light-emitting diodes FR and B, respectively were investigated in Eustoma grandiflorum under controlled temperature and 8-h sunlight. Flower budding was promoted by FR and B, while it was not observed under short-day conditions with an 8-h photoperiod during the treatment period. The flower budding with FR was earlier than with B. Expression analysis of flowering-related genes and potential light quality-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A similar control mechanism is possible for flowering because blue light delays flowering in tomato [ 53 , 54 ], and leaf SlFKF1 expression is also low under blue light. It is interesting to note that blue light promotes flowering in A. thaliana and some other long-day plants in contrast to tomato [ 10 , 21 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar control mechanism is possible for flowering because blue light delays flowering in tomato [ 53 , 54 ], and leaf SlFKF1 expression is also low under blue light. It is interesting to note that blue light promotes flowering in A. thaliana and some other long-day plants in contrast to tomato [ 10 , 21 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using Arabidopsis thaliana have shown that these photoreceptors control plant responses, including de-etiolation, hypocotyl elongation, and photoperiodic flowering by CRY [ 2 , 3 , 4 ] and phototropism, stomatal opening, and chloroplast localization by phototropin [ 5 , 6 , 7 , 8 ], indicating that their functions are diverse. Even in long-day plants other than A. thaliana , flowering promotion by blue light, which is supposed to involve CRY, has been reported in Petunia and Eustoma [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of flowering under blue light was consistently faster in both species, however, more pronounced in S. lateriflora than in S. baicalensis (Figure 3C, D). Blue light has previously been reported to be important for the onset and progression of flowering [49][50][51]. One month after the experimental period, leaf curling and drying in the tips were observed in both species under both light treatments.…”
Section: Blue Light Impacts Plant Growth and Floweringmentioning
confidence: 70%
“…Flowering is regulated by light quality; moreover, blue, red, and far-red wavelengths play crucial roles in plant photomorphogenesis and anthesis in Arabidopsis and horticultural plants [ 10 ]. Blue and far-red light promote flowering in Arabidopsis and Eustoma [ 11 , 12 ]. In addition to flowering, light quality can influence plant growth and metabolite accumulation in leafy vegetables [ 13 ].…”
Section: Introductionmentioning
confidence: 99%